N-(4-Chlorobutanoyl)-N′-[2-(trifluoromethyl)phenyl]thiourea - Yusof, Mohd Sukeri Mohd (International Union of Crystallography, 2012)
In the title compound, C(12)H(12)ClF(3)N(2)OS, the dihedral angle between the benzene ring and the thiourea fragment is 69.41 (5)°. The thiourea N—H atoms adopt an anti conformation, such that one of them forms an intramolecular N—H⋯O hydrogen bond, generating an S(6) ring. In the crystal, both N—H groups form inversion dimers, one via a pair of N—H⋯S hydrogen bonds and one via a pair of N—H⋯O hydrogen bonds. These lead to R (2) (2)(8) and R (2) (2)(12) loops, respectively. Weak C—H⋯Cl, C—H⋯F, C—H⋯S and π–π [centroid–centroid separation = 3.7098 (6)Å and slippage = 1.853 Å] interactions also occur.